Germinação e multiplicação in vitro de grápia (Apuleia leiocarpa (Vogel) J. F. Macbr.) - Lencina, Kelen Haygert (2013)
The objective of this study was to evaluate the in vitro germination and multiplication of grapia for plantlet production and conservation of selected genotypes. For in vitro establishment, three concentrations (0; 2.5 and 5.0%) of sodium hypochlorite (NaOCl) and seed immersion times of 5, 10 and 15 min were tested. Seeds were than inoculated in glass flasks with 5 mL of distilled water, sucrose (30 g L-1) and agar (7g L-1) medium. The evaluations were done at 30 days of cultivation for the percentage of germination and desinfestation, mean germination time (TMG) and germination speed index (IVG). Disinfected seeds were also inoculated in WPM (Wood Plant Medium) medium supplemented with 4, 5 or 6 g L-1 of agar combined with 10, 20 or 30 g L-1 of sucrose, and maintained under dark condition of the first seven days or light during the whole period of cultivation. The evaluations were done at 15 days for the percentage of germination, height of aerial part, number of leaves and internodes, total root length, TMG and IVG. Aseptic seedlings were transplanted to WPM, MS or ½ MS culture medium. After 15 days, they were evaluated for height of aerial part, total root length and number of internodes and leaves. The treatment of breaking seed dormancy associated with ethanol 70% promotes efficient desinfestation of grapia seeds, even without NaOCl immersion. Seeds maintained in dark showed the lowest TMG, the greatest IVG and the highest aerial part. The WPM medium supplemented with 4 g L-1 of agar and 10 g L-1 of sucrose is indicated for maintenance of grapia seedlings. For multiplication, segments of different positions (basal, medium and apical) were inoculated in WPM medium supplemented with 0; 2.2; 4.4; 6.6 or 8.8 μM of 6-benzylaminopurine (BAP). Nodal segments were inoculated in WPM medium supplemented with 0; 2.2; 4.4; 6.6 or 8.8 μM of BAP and 0 and 1.5 g L-1of activated charcoal. Nodal segments were also inoculated in WPM medium supplemented with 0; 2.3; 4.6; 6.9 and 9.2 μM of kinetin (KIN) and 0 and 1.5 g L-1of activated charcoal. The three experiments were evaluated at 30 days for the presence of callus, number and total length of sprouts, number of leaves, rooting percentage, and number and total length of roots. Microstumps were maintained in WPM medium with 0; 2.2; 4.4; 6.6 and 8.8 μM of BAP and 0 and 1.5 g L-1of activated charcoal. After 30 days, microstumps were subcultured in WPM medium with 1.5 g L-1 of activated charcoal. After 30 days of cultivation in BAP and subcultivated in activated charcoal, microstumps were evaluated for survival, percentage of sprouting, number and total length of sprouts and number of internodes and leaves. Basal segments showed the greatest number and length of sprouts. The WPM medium supplemented with 6.6 μM of BAP resulted in the greatest number of sprouts. The activated charcoal reduced callus formation and favored root formation. KIN didnot favor sprout formation. The WPM medium supplemented with 8.8 μM of BAP increases the number of sprouts and leaves in microstumps subcultivated in WPM medium with 1.5 g L-1 of activated charcoal.